Improving Studens' Reading Comprehension Using SQ3R Reading Technique for The XII IPS-2 students of SMA Negeri Gondangrejo Karanganyar in the Academic Year 2009-2010 - Rudatin, Siwi (2012)
This study is an action research. General objective of this study is improving students' reading comprehension using SQ3R reading technique, while the specific objectives of this research are (1) to find out whether or not SQ3R reading technique can improve students' reading comprehension for the XII IPS-2 students of SMA Negeri Gondangrejo Karanganyar in the academic year 2009-2010, (2) to find out information about students' motivation toward the use of SQ3R reading technique (3) to find out the strengths and the weaknesses of the use of SQ3R reading technique in improving students' reading comprehension. This action research was conducted at SMA N Gondangrejo Karanganyar. The procedure of the research consisted of planning, action, observation, and reflection. The data were collected using non-observational and observational technique supported with test. The non-observational techniques used interviews. The observational techniques consisted of observation, checklist, field notes, and photographs. The observation during the process of English teaching and learning was conducted with the help from collaborator. In this research, the writer acted as the practitioner. The tests were in the form of post-test conducted at the end of first cycle, second cycle, and third cycle. The research resulted: (1) the use of SQ3R reading technique can improve students' reading comprehension of the XII IPS-2 students of SMA Negeri Gondangrejo Karanganyar in the academic year 2009-2010. It is approved by the increase of students' average score in reading comprehension test from 57.38 in the first cycle to 62.81 in the second cycle and to 70.94 in the third cycle. In the end of the third cycle 87.5 % of students got score as high as or more than 60. (2) Students' motivation toward the use of SQ3R reading technique in the teaching and learning reading was very good. This was proved by the increase of students' motivation, participation and engagement in the process of teaching and learning reading. (3) The use of SQ3R Reading technique has many strengths and weaknesses. The strengths are : (a) The use of SQ3R reading technique can help students setting their goal of reading, (b) The use of SQ3R actively engages students as they study, (c) The review techniques helps students fix information in their mind. The weaknesses are: (a) Time consuming and need more guidance from teacher (b) The step of questioning is quite difficult for student because they don't have proper skill in asking question and in using the correct structure and (c) The step of reciting is quite difficult because of the students' limited vocabulary,